Prebiotic effect of purple sweet potato resistant starch and the development of its mucoadhesive granule formulation - Yuniarni, Umi; Aryani, Ratih; Rusdi, Bertha; Nabilla, Qori (Pharmaciana, 2025)
Purple sweet potatoes are recognized for their prebiotic properties including againts Lactobacillus casei and L. bulgaricus bacteria. This prebiotic effect is due to the high starch content in purple sweet potatoes. The amylose content in starch which is difficult to digest in gastointestinal tract, functions as a prebiotic. To enhance the prebiotic effect of purple sweet potato starch, modification into resistant starch can be performed. Resistant starch exhibits a higher prebiotic effect compared to regular starch because it cannot be broken down by digestive enzymes, allowing it to reach the large intestine in significant amounts. Additionally, the prebiotic effect can be further enhanced by creating mucoadhesive granule formulations that increase the contact time of a substance on the mucosa of the digestive tract. This study aims to evaluate the prebiotic effect of resistant starch from purple sweet potatoes and to develop its mucoadhesive granule formulation. The resistant starch from purple sweet potatoes was prepared using the heat moisture treatment method. The prebiotic activity of resistant starch was tested against Lactobacillus acidophilus and Escherichia coli. The granule formulation was prepared by varying the concentration of polymers used, namely a combination of HPMC and carbopol as mucoadhesive polymers. The results showed that resistant starch from purple sweet potatoes had a prebiotic index of 0.930. The granule formulation F3 with an HPMC and Carbopol polymer ratio of 1:2 was identified as a good mucoadhesive granule formulation. It met pharmaceutical evaluation with a mucoadhesive percentage value of 40%.